Dampak Reuni Sekolah Terhadap Keharmonisan Rumah Tangga Perspektif Urf - Riziq Ahmad Pulungan; Abd Mukhsin (Institut Agama Islam Negeri Ponorogo, 2025)
This study examines in depth the impact of school reunions on household harmony from the perspective of ‘urf among the community of Gedung Johor Village, Medan City. This phenomenon is important to explore because reunions, which ideally aim to strengthen social ties and expand networks, often become a source of tension within families due to intensive interactions with former classmates, particularly those of the opposite sex. The purpose of this study is to analyze how the community interprets reunions within the context of ‘urf and their implications for family harmony. This research employs a qualitative method with a case study approach. Data were obtained through in-depth interviews with married couples who attended reunions, religious leaders, and community members, complemented by field observations and documentation. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings show that most residents of Gedung Johor consider reunions to be ‘urf sahih when conducted with proper manners, transparency with spouses, and without neglecting family responsibilities. However, reunions that lead to jealousy, distrust, or infidelity—resulting in household conflict—are viewed as ‘urf fasid because they contradict Islamic principles and social norms. Thus, reunions should be carried out within the boundaries of religious values and local culture to remain a means of strengthening social ties and avoiding harm to family harmony.